Characterization of Composite Electron Sources (Metal - Insulator - Vacuum) - A. M. Al-Qudah,; S. S. Alnawasreh,; M. A. Madanat,; O. Trzaska,; D. Matykiewicz,; S. S. Alrawshdeh,; M. J. Hagmann,; M. S. Mousa, (Jordan Journal of Physics, 2025)
Field electron emission measurements were performed on composite tips (Insulator- Tungsten) that were prepared by electrochemical etching in NaOH solution. The current-voltage (I-V) characteristics and field electron emission images were recorded under UHV conditions with a base pressure of <10-9 mbar. Next, the tips were coated with several different types of dielectric layers. Various techniques were employed to measure the characteristics of these types of emitters and to evaluate the effects of different types of dielectric coatings on the performance and reliability of such an electron source. Keywords: Field electron emitter, Dielectric layers, Composite tip, Field electron microscope.